2016
DOI: 10.1093/pm/pnw080
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Demographic, Clinical, Symptom and Psychological Characteristics on the Trajectories of Acute Postoperative Pain After Total Knee Arthroplasty

Abstract: Objective. Total knee arthroplasty is a painful procedure. No studies have evaluated modifiable predictors of acute postoperative pain trajectories during hospitalization.Methods. Consecutive patients (N = 188) were enrolled in a longitudinal cohort study and completed a demographic questionnaire, as well as the Brief Pain Inventory, Hospital Depression and Anxiety Scale, Lee Fatigue Scale, Fatigue Severity Scale, and Brief Illness Perception Questionnaire on the day before surgery. Clinical data were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 55 publications
1
43
0
Order By: Relevance
“…This suggests that the association between pain intensity and opioid consumption goes beyond the pain experience and is multifactorial. While a significant body of literature has found an association between levels of acute post-operative pain intensity and opioid consumption, (Lindberg et al, 2017;Maheshwari et al, 2016) such association has not been found in other studies (Seong Tan, Nik Mohamad, & Gan, 2013) or has been shown to vary with respect to the strength of association based on variables such as age (Gagliese, Gauthier, Macpherson, Jovellanos, & Chan, 2008). The association between pain intensity and opioid consumption in the days following surgery might be influenced or mediated by other factors, such as psychological distress or peri-operative factors.…”
Section: Repartition Of Patients Into the Pain And Opioid Consumptimentioning
confidence: 95%
See 1 more Smart Citation
“…This suggests that the association between pain intensity and opioid consumption goes beyond the pain experience and is multifactorial. While a significant body of literature has found an association between levels of acute post-operative pain intensity and opioid consumption, (Lindberg et al, 2017;Maheshwari et al, 2016) such association has not been found in other studies (Seong Tan, Nik Mohamad, & Gan, 2013) or has been shown to vary with respect to the strength of association based on variables such as age (Gagliese, Gauthier, Macpherson, Jovellanos, & Chan, 2008). The association between pain intensity and opioid consumption in the days following surgery might be influenced or mediated by other factors, such as psychological distress or peri-operative factors.…”
Section: Repartition Of Patients Into the Pain And Opioid Consumptimentioning
confidence: 95%
“…While this is also true of acute post‐surgical pain, fewer articles have been published on the association between peri‐operative opioid consumption and CPSP outcomes (Katz et al., ; Schug & Bruce, ). Research suggests, however, that acute post‐operative pain and opioid consumption are strongly associated (Lindberg et al., ; Maheshwari et al., ). Recently, studies have moved beyond simple static measures of acute pain to examine profiles of pain trajectories and how they relate to long‐term outcomes (Chapman, Davis, Donaldson, Naylor, & Winchester, ; Chapman, Donaldson, Davis, & Bradshaw, ; Chapman, Fosnocht, & Donaldson, ; Page et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Surgery can be an option to relieve pain in rheumatoid arthritis, osteoarthritis and back conditions (Boonen and Severens, 2011 ; Gore et al, 2012 ; Xie et al, 2016 ). A large number of psychological aspects related to pain, such as anxiety, depression, cognitions, expectations and personality traits can be considered as strong predictors of the outcomes of these interventions (Schade et al, 1999 ; Trief et al, 2000 ; DeBerard et al, 2003 ; Kohlboeck et al, 2004 ; den Boer et al, 2006 ; Abbott et al, 2011 ; Judge et al, 2012 ; Block et al, 2013 ; Akins et al, 2015 ; Anderson et al, 2015 ; Kunutsor et al, 2016 ; Alattas et al, 2017 ; Lindberg et al, 2017 ; Mancuso et al, 2017 ). Each of these factors seems to differently affect the various outcomes of the treatment, leading to a boost of the direct and indirect costs of the care.…”
Section: Economic Utility Of the Assessment Of The Psychological Varimentioning
confidence: 99%
“…It has primarily been used among adults with cancer [4,5] and human immunodeficiency virus (HIV) [6,7]. However, it has also been used in other populations such as patients admitted to intensive care units [8], undergoing knee arthroplasty [9], stroke [10] and living with chronic obstructive pulmonary disease [11]. Nonetheless, PROMs with strong psychometric properties in one population need to be evaluated for use in other patient populations.…”
Section: Introductionmentioning
confidence: 99%